2020
DOI: 10.24259/fs.v4i2.10309
|View full text |Cite
|
Sign up to set email alerts
|

Indicators to Evaluate the Institutional Effectiveness of National Climate Financing Mechanisms

Abstract: Over the past few decades, tackling climate change has persistently featured in international discussions, with the main issues centring on mobilising adequate global response and effectively coordinating and channelling this response at the sub-national levels. In order to effectively mobilize and harmonize resources to address climate change at country level, the idea of establishing national climate finance institutions (NCFIs) with the duty to mobilise, manage and allocate funds to implement climate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
8
0
4
Order By: Relevance
“…It can be used to evaluate the impacts of ecosystem change on economic activity, among others (UN et al 2014). There has been an increased number of studies related to ecosystem accounting in Indonesia, to assess the physical and monetary value of ES (Sumarga and Hein 2014;Suwarno et al 2016), to integrate environmental value into the fiscal policy (Nurfatriani et al 2015), to develop indicators for a green financing mechanism (Sheriffdeen et al 2020), to utilize non-timber forest products (Adalina et al 2014), and to use spatial information of ES as the basis for future forest governance and land use strategy (Sumarga and Hein 2014; J o u r n a l P r e -p r o o f al. 2017; Suwarno et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to evaluate the impacts of ecosystem change on economic activity, among others (UN et al 2014). There has been an increased number of studies related to ecosystem accounting in Indonesia, to assess the physical and monetary value of ES (Sumarga and Hein 2014;Suwarno et al 2016), to integrate environmental value into the fiscal policy (Nurfatriani et al 2015), to develop indicators for a green financing mechanism (Sheriffdeen et al 2020), to utilize non-timber forest products (Adalina et al 2014), and to use spatial information of ES as the basis for future forest governance and land use strategy (Sumarga and Hein 2014; J o u r n a l P r e -p r o o f al. 2017; Suwarno et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study is to examine the institutional effectiveness of the FNMC from 2009 to 2020, by employing these five dimensions, as proposed by Sheriffdeen et al (2020). This is an exploratory study, and it adopted documentary research as the technical data collection method.…”
Section: Sheriffdeenmentioning
confidence: 99%
“…The authors employ the term "institutional effectiveness" to refer to institutional capacity for attracting and managing climate finance appropriately, and to monitor and evaluate impacts. Through an extensive literature review on climate finance frameworks and principles, Sheriffdeen et al (2020), identified 21 indicators, which they categorized into five dimensions:…”
Section: Introductionmentioning
confidence: 99%
“…P. Hmyria et al, 2019). The tremendous economic potential of forest resources can be used as capital in developing the forestry sector (Nurfatriani et al, 2015;Sheriffdeen et al, 2020). However, the performance of the forestry sector in the economy tends to decline (Asosiasi Pengusaha Hutan Indonesia, 2019;Mäkelä, 2017;Zendrato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%